Do changing institutional settings matter? Educational attainment and family related employment interruptions in Germany - Katrin Drasch (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2011)
Cross-sectional studies show that in West Germany women with different levels of educational attainment participate differently in the labor market. In this paper, I examine one potential underlying mechanism: the re-entry of mothers in the labor market after a period of inactivity. I argue that besides societal changes the reforms of parental leave legislation could be responsible for the educational divide in mothers' employment. Hypotheses are derived from human capital theory and labor supply theory assuming a rational behavior of women. Using retrospective life-course data from the IAB study ALWA, I find evidence that women with different levels of educational attainment have different re-entry patterns also when taking the educational attainment of the partner into account. Furthermore, parental leave schemes play a crucial role for re-entries. Some evidence of an educational polari-zation of re-entry behavior is found after the year 2000. – – Auf Basis von Analysen mit Querschnittdaten wurde festgestellt, dass sich die Ar-beitsmarktpartizipation von Frauen in Westdeutschland nach deren Bildungsgrad unterscheidet. In diesem Papier untersuche ich einen potentiellen, zugrundeliegen-den Mechanismus: den Wiedereintritt von Müttern in den Arbeitsmarkt nach einer Inaktivitätsphase. Ich argumentiere, dass neben gesellschaftlichen Veränderungen die Reformen in der Gesetzgebung zu Erziehungszeiten für die bildungsspezifische Ungleichheitsentwicklung verantwortlich sein könnten. Die Ableitung der Hypothesen erfolgt aus der Humankapitaltheorie und der Arbeitsangebotstheorie. Hier wird eine rationale Handlungsweise der Frauen unterstellt. Mittels retrospektiver Lebens-verlaufsdaten der IAB-ALWA Studie wird festgestellt, dass Frauen mit unterschiedlichem Bildungsniveau auch unter Berücksichtigung des Bildungsniveaus des Partners unterschiedliche Wiedereinstiegsmuster aufweisen. Schließlich spielen Regelungen zu Erziehungszeiten eine entscheidende Rolle für den Wiedereinstieg. Zudem gibt es Anzeichen für eine bildungsspezifische Polarisierung des Wiedereinstiegsverhaltens nach dem Jahr 2000.
Keywords: C41; J18; J24; 330; maternal employment; parental leave legislation; discrete-time event history analysis; Frauen; Bildungsniveau; Elternzeit; Berufliche Integration; Deutschland